Archaeology and the social history of ships - Gould, Richard A. (Cambridge Cambridge University Press, 2011)
"This book is intended for scholars, students, administrators, and workers in historic preservation and resource management, and sport divers wishing to understand shipwrecks as a cultural resource. In this book, shipwrecks emerge as a "mother lode" of scientifically credible information how human societies went to sea"--Provided by publisher.
Also available in eBook format.
Keywords: Underwater archaeology; Shipwrecks; Ships -- History; Ocean and civilization